2019
DOI: 10.1016/j.jcrc.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Influenza virus and factors that are associated with ICU admission, pulmonary co-infections and ICU mortality

Abstract: a b s t r a c t a r t i c l e i n f oPurpose: While most influenza patients have a self-limited respiratory illness, 5-10% of hospitalized patients develop severe disease requiring ICU admission. The aim of this study was to identify influenza-specific factors associated with ICU admission and mortality. Furthermore, influenza-specific pulmonary bacterial, fungal and viral co-infections were investigated. Methods: 199 influenza patients, admitted to two academic hospitals in the Netherlands between 01-10-2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
100
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 36 publications
12
100
6
Order By: Relevance
“…Bacterial coinfection was identified in approximately one third of fatal influenza A(H1N1)pdm09 cases in the largest autopsy case series [31]. Bacterial co-infections in the interpandemic period are also common in critically ill influenza patients [32]. One study identified past or current tobacco use as a risk factor associated with ICU admission [33].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Bacterial coinfection was identified in approximately one third of fatal influenza A(H1N1)pdm09 cases in the largest autopsy case series [31]. Bacterial co-infections in the interpandemic period are also common in critically ill influenza patients [32]. One study identified past or current tobacco use as a risk factor associated with ICU admission [33].…”
Section: Risk Factorsmentioning
confidence: 99%
“… 3 Since pneumocystosis is usually reported in patients with T-cell immunodepression, 4 less attention has been paid to Pneumocystis jirovecii in non-immunocompromised ICU patients although it accounts for 7% of the co-infections reported in those admitted with Influenza. 5 Interestingly, COVID-19 patients may develop lymphocytopenia and acute respiratory distress syndrome (ARDS) requiring adjunctive steroids and/or immunomodulatory therapies, well-known susceptibility factors for developing pneumocystosis. 5 We designed this observational cohort study to investigate the prevalence of P. jirovecii acid nucleic detection in respiratory specimens sampled to identify co-infections in COVID-19 patients in the ICU.…”
mentioning
confidence: 99%
“… 5 Interestingly, COVID-19 patients may develop lymphocytopenia and acute respiratory distress syndrome (ARDS) requiring adjunctive steroids and/or immunomodulatory therapies, well-known susceptibility factors for developing pneumocystosis. 5 We designed this observational cohort study to investigate the prevalence of P. jirovecii acid nucleic detection in respiratory specimens sampled to identify co-infections in COVID-19 patients in the ICU.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the following reasons: (1) At the beginning of statistical analysis, all cases with missing BMI data and outliers were excluded from the study; (2) The first study by Seung Hyeok Han enrolled 212 patients with AKI undergone CRRT, which was significantly smaller compared to our study, thus the conclusion of our study was more reliable. (3) The second study by Seung Hyeok Han adjusted the following variables: age, sex, CCI score, septic AKI, MAP, eGFR, SOFA score, WBC, Alb and CRRT dose, but did not adjust for the following variables: myocardial infarction, diabetes, congestive heart failure and hypertension, CRP, AKI cause, mechanical ventilation and phosphate which had been reported to occur in critically ill patients [13][14][15][16][17]. (4) We tested the collinearity of the variables included in the statistical analysis, and found that VIF of all variables was less than 2, hence there was no statistical collinearity in the included variables.…”
Section: Discussionmentioning
confidence: 99%